Interpolation based pilot-aided channel estimation for STBC spatial modulation and performance analysis under imperfect CSI - Doğan, Hakan; Başar, Ertuğrul; Panayırcı, Erdal; ACAR, YUSUF; GÜNTEKİN, BAHAR (INST Engineering Technology-Iet, Michael Faraday House Six Hills Way Stevenage, Hertford Sg1 2Ay, England, 2016)
A combination of space-time block coding and spatial modulation (STBC-SM) has been recently proposed for multiple input-multiple output systems to obtain both spatial diversity gain and more capacity simultaneously while assuming the perfect channel state information (P-CSI) was available at the receiver. However, in practical scenarios the CSI is unknown to the receiver and should be estimated in order to detect the transmitted data in a reliable way. Therefore, channel estimation (CE) is a major challenge in designing the STBC-SM systems. In this study, the problem of CE is investigated and a new pilot-aided channel estimation (PA-CE) technique, coupled with an interpolation, is proposed for the STBC-SM systems operating in the presence of rapidly time-varying mobile channels. Several interpolation schemes such as the linear, nearest neighbour, piecewise cubic Hermite and the low-pass interpolations are applied and their performances are compared to determine the best suitable interpolation technique to be employed in STBC-SM systems. Bit error rate (BER) performance of the proposed CE technique is then investigated in time-varying channels with different modulation. Moreover, the pairwise error probability of the STBC-SM scheme is derived and its average bit error probability is evaluated analytically in the presence of CE errors.
Keywords: channel estimation; space-time block codes; diversity reception; MIMO communication; interpolation; mobile radio; time-varying channels; error statistics; quadrature phase shift keying; quadrature amplitude modulation; interpolation-based pilot-aided channel estimation; STBC spatial modulation; imperfect CSI; space-time block coding; multiple-input multiple-output systems; spatial diversity gain; perfect channel state information; P-CSI; STBC-SM systems; PA-CE technique; time-varying mobile channels; linear nearest neighbour piecewise cubic Hermite; low-pass interpolation; bit error rate performance; BER performance; quadrature phase shift keying; QPSK; 16-quadrature amplitude modulation; 16-QAM; 64-QAM; pairwise error probability; bit error probability; Spline Interpolation; Systems; Diversity